Detection of Knockdown-Resistance Mutations (V1016G and F1534C) in Dengue Vector from Urban Park, Surabaya, Indonesia - Shifa Fauziyah; Sri Subekti; Budi Utomo; Teguh Hari Sucipto; Hebert Adrianto; Aryati Aryati; Puspa Wardhani; Soegeng Soegijanto (Universitas Gadjah Mada, 2021)
An urban park is potentially a source of vector-borne disease transmission due to it being a natural and artificial mosquito breeding habitats combined with people's continuous presence. Thus, this study aims to screen the occurrence of knockdown-resistance (kdr) mutant alleles (V1016G and F1534C) in mosquito populations collected from urban parks in Surabaya, Indonesia. Cross sectional study was conducted in July 2019. A total of 28 ovitraps were installed in seven urban parks, having four ovitraps installed in each park. In total, 1,662 eggs were collected, and only 187 emerged into adult mosquitoes, consisting of 97 Aedes (Stegomyia) aegypti and 90 Aedes (Stegomyia) albopictus. All-female adult mosquitoes (n=55) were tested using allele-specific polymerase chain reaction assay (AS-PCR) to detect voltage gated sodium channel (VGSC) gene mutations. This study found no mutations in Valine to Glysine mutation in point 1016 (V1016G) and Phenylalanine to Cysteine in point 1534 (F1534C) alleles in both two species. All of mosquito samples have wild type genotype of kdr alleles (V1016V and F1534F). Data were analysed using R Studio 1.4 Version by Genetics package. Results showed that the frequency of resistant alleles (G1016 and C1534) was zero, and the frequency of susceptible allele was 1 (V1016 and F1534). Insecticide bioassay could not be established due to the limited number of adult mosquitoes, so insecticide resistance status could not be determined. However, this study can be used as preliminary monitoring for the vector control program.